Polimorfismo-174(G/C) na regiao promotora do gene da interleucina 6 e o risco de cancer de colo do utero: estudo caso-controle - Nogueira-de-Souza, Naiara Corrêa [UNIFESP] (2006)
Recent data implicate that cytokine gene polymorphisms are important in pathogenesis of various neoplastic and nonneoplastic human diseases, and it was recently suggested that polymorphisms in interleukin (IL)-6 might increase the risk of gynecological malignancies, including cervical carcinomas. The aim of this case-control study is to compare the IL-6 polymorphisms in cervical cancer patients and healthy controls and to assess whether any of these polymorphisms would increase the risk of developing cervical cancer. The material in this case-control study consists of 56 patients with cervical carcinoma and 253 population based control subjects, all ethnic Brazilian women. Control subjects were cancer-free women, following a negative cervical cytology and colposcopy. IL-6 genotyping was performed using a polymerase chain reaction–based restriction fragment length polymorphism. Distribution of the GG, GC, and CC genotypes in cases and controls was significantly different (P=0.033). Compared with the GG genotype as reference, the adjusted odds ratio for the combined GC and CC genotypes in cancer patients was 1.90 (95% confidence interval, 1.1–3.4). These data suggest that women carrying at least one C genotype in their IL-6 promoter region (–174G/C) are at higher risk of developing cervical cancer.